(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2024)
The article analyses the environmental factors i.e. abiotic conditions of adaptation and introduction of the woody plant Paulownia Siebold & Zucc growing in the local conditions of Kazakhstan. The Paulownia tree naturally grows in China and is now cultivated in various other countries. There are approximately 9 natural species known, as well as many hybrid species. The spectrum of uses for the Paulownia tree is broad: agroforestry and land reclamation, pulp industry, biofuel and biomass production, timber harvesting, phytoremediation, and reclamation, among others, making it of significant practical value. The Paulownia plant has been cultivated in Kazakhstan for the past 5-6 years and is growing and developing in the southern and southeastern regions of the country. In Kazakhstan, the Paulownia plant has been recently introduced and transplanted, so biological and ecological studies of the Paulownia in local environmental conditions have not yet been conducted. Our research is being carried out in the villages of Uzynagash and Beriktas in the Zhambyl District of Almaty City and the Almaty Region. For the purpose of the study, climatic and edaphic factors of the examined area were considered and analyzed to assess the impact of local abiotic factors on the growth of hybrid species of the Paulownia family. Thus, the agroclimatic conditions and agrochemical properties of the soil in Almaty City and the Almaty Region are suitable for planting Paulownia trees Keywords: Paulownia Siebold & Zucc, abiotic factors, tolerance, adaptation